Transformasi Nilai dalam Perayaan Maulid Nabi: Mengidentifikasi Penyimpangan dalam Tradisi Religius di Desa Jambe Kecamatan Kertasemaya Kabupaten Indramayu - Aliyatus Sholikah; Akhmad Affandi; Noor Ayu Fathimah3 (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The celebration of the Prophet's birthday in Jambe Village, which has been going on for generations as a religious and cultural tradition, shows a change in values in recent years. This change is reflected in the emergence of behavior that is considered deviant, such as excessive entertainment and lack of attention to spiritual aspects. This phenomenon indicates a transformation of values due to the influence of modernization which affects the balance between religious values and local culture. This article aims to: 1) Identify the religious and cultural values contained in the celebration of the Prophet's birthday in Jambe village. 2) Analyze the value transformation that occurs during the celebration. 3) Explore the factors that cause the transformation of values in the celebration of the Prophet's birthday in Jambe village. This research uses a qualitative method with a descriptive approach to reveal facts in depth based on existing conditions. The location of the research was Jambe Village, Kertasemaya District, Indramayu Regency. Data sources consist of primary data through observations and interviews with the Prophet's birthday celebration committee, religious leaders, village government, and residents of Jambe Village, as well as secondary data in the form of related documents. In Jambe Village, the Prophet's Birthday Celebration combines religious and cultural values such as love, care, honesty, example, spirit of worship, and cultural enrichment through traditional music. However, significant values change with time. The essence of the celebration, which was originally full of religious meaning, began to shift. As a result, there are difficulties in maintaining the original values of the Prophet's birthday.